2004
DOI: 10.1109/tase.2004.829427
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Estimation and Testing for Variation Root-Cause Identification of Multistage Manufacturing Processes

Abstract: Abstract-Root-cause identification for quality-related problems is a key issue in quality and productivity improvement for a manufacturing process. Unfortunately, root-cause identification is also a very challenging engineering problem, particularly for a multistage manufacturing process. In this paper, root-cause identification is formulated as a problem of estimation and hypothesis testing of a general linear mixed model. First, a linear mixed fault-quality model is built to describe the cause-effect relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(31 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…The typical statistical estimation algorithms are ML estimation, restricted ML estimation (REML), and minimum norm quadratic unbiased estimation (MINQUE) (see Rao and Kleffe 1988). Zhou et al (2004) suggested using MINQUE as an approximation of the ML estimate for multistage models because the computation load of MINQUE is much lower than that of ML estimation or REML. But we do not believe that MINQUE is suitable for phase I analysis, for two reasons.…”
Section: The Directional Multivariate Change Point Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The typical statistical estimation algorithms are ML estimation, restricted ML estimation (REML), and minimum norm quadratic unbiased estimation (MINQUE) (see Rao and Kleffe 1988). Zhou et al (2004) suggested using MINQUE as an approximation of the ML estimate for multistage models because the computation load of MINQUE is much lower than that of ML estimation or REML. But we do not believe that MINQUE is suitable for phase I analysis, for two reasons.…”
Section: The Directional Multivariate Change Point Methodsmentioning
confidence: 99%
“…Xiang and Tsung (2006) and Zantek, Gordon, and Robert (2006) considered online monitoring and diagnosis of out-of-control (OC) conditions in the multistage process. Zhou, Chen, and Shi (2004) estimated the process parameters by applying the typical estimation methods of general mixed linear models. Xiang and Tsung (2006) alternatively derived an EM procedure for maximum likelihood (ML) estimates of the parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, the SoV model has been applied for a large number of applications such as part quality estimation and process planning [9][10][11], manufacturing fault identification [12][13][14][15][16][17][18][19][20], dimensional quality control [21][22][23][24][25][26] and process-oriented tolerancing [27,28].…”
Section: Main Applicationsmentioning
confidence: 99%
“…Besides analyzing the diagnosis capability of the MMP, other research works have also studied how to identify a specific root fault cause when it is diagnosable. For this purpose, pattern recognition techniques [16] and direct estimation methods [15] have been tested.…”
Section: Fault Cause Identificationmentioning
confidence: 99%